Hierarchical pore catalyst for directly preparing isohydrocarbon from synthesis gas as well as preparation method and application of hierarchical pore catalyst
By using SBA-15 catalyst with multi-stage pore structure and introducing active cobalt species in combination with ultrasonic assisted vacuum impregnation, the problems of insufficient thermal stability, hydrothermal stability and isomer hydrocarbon selectivity in the prior art are solved, and an efficient process for direct isomer hydrocarbon production in synthesis gas is achieved, with concentrated product distribution and low cost and energy consumption.
Patent Information
- Application Number
- CN202411724752.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-02-28
AI Technical Summary
In the prior art, in the process of direct production of isomeric hydrocarbons in synthesis gas, there is still room for improvement in the thermal stability, hydrothermal stability and isomeric hydrocarbon selectivity of the catalyst, resulting in insufficient product distribution and high cost and energy consumption.
Using a multi-stage pore catalyst composed of metal cobalt, additives and carriers, the active cobalt species are introduced through ultrasonic-assisted vacuum impregnation method to form a SBA-15 catalyst with a microporous-mesoporous-macroporous structure. The catalyst maintains the multi-stage pore structure unchanged under high temperature calcination and hydrothermal conditions, which improves the thermal stability and hydrothermal stability of the catalyst.
The CO conversion rate was achieved at 60-90%, CH4 <5%, C2-C4 <5%, C5-C18 ≥60%, C18+ <30%, CO2 <2%. The multi-stage pore structure of the catalyst remained unchanged, significantly improving the selectivity and stability of isomer hydrocarbons.
Abstract
Description
Technical Field
[0001] The invention relates to the field of direct preparation of isomerized hydrocarbons from synthesis gas. Background Art
[0002] In recent years, researchers in related fields have been committed to solving the problem of wide selectivity distribution of Fischer-Tropsch synthesis products, with the goal of breaking the traditional ASF distribution and achieving selective regulation of products. Usually, after reforming the Fischer-Tropsch products (such as hydrocracking and isomerization), target products with very narrow distribution, such as gasoline and diesel components, can be obtained. However, additional equipment increases costs and wastes energy. Therefore, researchers are committed to directly synthesizing intermediate distillates with high isomer component selectivity from synthesis gas in one step. This process combines the Fischer-Tropsch synthesis reaction with hydrocracking and isomerization reactions, thereby reducing energy consumption, improving cost utilization, and has a relatively good application prospect.
[0003] In recent years, the combination of zeolite molecular sieves and Fischer-Tropsch synthesis catalysts to prepare bifunctional catalysts has attracted widespread attention. This method aims to reduce the cost of the reforming process and maximize the proportion of liquid fuel in the Fischer-Tropsch synthesis product. Using acidic zeolites as carriers or co-catalysts for cobalt-based Fischer-Tropsch synthesis catalysts can make the Fischer-Tropsch products deviate from the ASF distribution and increase the selectivity of isomeric components in the product. In this catalytic system, the primary products generated at the active sites of the Fischer-Tropsch catalyst move to the micropores of the zeolite molecular sieve for cracking and isomerization reactions. The bifunctional catalyst obtained by directly mechanically mixing the zeolite molecular sieve and the Fischer-Tropsch active component and the capsule bifunctional catalyst with a zeolite molecular sieve as the shell are currently two widely used systems. However, because the Fischer-Tropsch active site and the acid site of the zeolite molecular sieve are far apart in the physically mixed catalyst, a large part of the Fischer-Tropsch product directly diffuses into the catalyst bed, thereby losing the opportunity for further reforming, resulting in low selectivity for isomeric components and a relatively wide distribution of products. Encapsulated cobalt-based catalysts solve this problem very well. The long-chain products produced at the active sites of the Fischer-Tropsch catalyst in the core can be fully hydrocracking and isomerization reforming through the zeolite molecular sieve in the shell to obtain highly isomerized components. However, in this process, the microporous structure of the zeolite molecular sieve is very unfavorable for the mass transfer and diffusion of reactants and products, which often leads to excessive cracking and the production of a large amount of gaseous products with high methane selectivity.
[0004] In order to solve this problem, many researchers began to prepare zeolites with hierarchical pore structures, using their good pore structures to solve the diffusion limitation problem. Wang Ye's research group at Xiamen University prepared microporous-mesoporous ZSM-5 by etching microporous ZSM-5 molecular sieves with NaOH, and loaded metal ruthenium for Fischer-Tropsch synthesis. They found that the C5-C11 gasoline selectivity of Ru / meso-ZSM-5 catalyst was as high as 80%, and the isomerized hydrocarbon / alkane ratio was also 2.7. However, the diffusion performance and hydrothermal stability of the micro-mesoporous composite or hierarchical pore catalysts reported in the past could not be improved at the same time, and their application in the field of catalysis is still limited. Therefore, the research on the preparation and application of confined hierarchical pore structure bifunctional catalysts not only helps to have a deeper understanding of the nature of catalysis, but also has important academic value and practical significance because of its efficient reactant and product diffusion performance, high mass transfer and heat transfer performance, and strong hydrothermal stability.
[0005] The patent with publication number CN101327442A discloses a hydrocarbon catalyst with high isohydrocarbon content from synthesis gas, a preparation method and an application thereof. The catalyst is based on the synergistic effect of bifunctional catalytic components, and a novel Fischer-Tropsch synthesis catalyst with high isohydrocarbon content in the export product of the Fischer-Tropsch synthesis reactor is prepared by loading Co on a molecular sieve or co-doping a Co-based Fischer-Tropsch synthesis catalyst with a molecular sieve. The prepared catalyst has a very high selectivity for isohydrocarbons (branched alkanes), can significantly improve the oil quality of the gasoline fraction section, and also reduces the condensation point of the diesel fraction section, greatly increases cold resistance, effectively reduces the load of the downstream section, and improves the economy of the process. The most notable feature is that when the catalyst of the present invention is used for the Fischer-Tropsch synthesis reaction, the catalyst activity is generally high, and the selectivity of gaseous light hydrocarbons such as methane in the product is low, the process stability is good, and in particular, the product selectivity will not be significantly reduced as the reaction proceeds. However, the thermal stability, hydrothermal stability and isohydrocarbon selectivity of the catalyst still have the potential for further improvement. Summary of the invention
[0006] The technical problem to be solved by the present invention is: how to provide a multi-level porous catalyst for directly preparing isohydrocarbons from synthesis gas with higher isohydrocarbon selectivity and higher thermal stability and hydrothermal stability.
[0007] The technical scheme adopted by the present invention is: a multi-level porous catalyst for directly preparing isohydrocarbons from synthesis gas, the multi-level porous catalyst is composed of active components, additives and carriers, and the weight percentage composition is: metal cobalt: 2-30%, metal additive content 0-10%, shell carrier 65-90%, the carrier is a multi-level porous SBA-15 composed of micropores, mesopores and macropores; metal cobalt and metal additives are used as the inner core and are wrapped by the shell carrier, the particle diameters of the metal cobalt and metal additives are 2-10 nm, and the thickness of the shell carrier is 50-600 nm.
[0008] The multi-level porous catalyst has a specific surface area of 300-1500 m2 / g, a pore volume of 0.2-2.5 cm3 / g, a micropore size of 0.3-1.6 nm, a mesopore size of 3-25 nm, a macropore size of 50-600 nm, and a catalyst particle diameter of 50-1200 nm.
[0009] The metal additive is one or two of manganese, zirconium, silver, ruthenium, lanthanum, cerium, calcium, magnesium, barium and the like.
[0010] The hierarchical pore structure of the multi-level porous catalyst remains unchanged when the catalyst is calcined at 400-650 ℃, and the hierarchical pore structure of the catalyst remains unchanged when the catalyst is boiled at 100-150 ℃ for 10 h.
[0011] When the multi-level porous catalyst is used, the CO conversion rate reaches 60-90%, and the mass percentage content of the product is: CH4<5%, C2-C4<5%, C5-C 18 ≥ 60%, C 18 + <30%, CO2< 2%.
[0012] A method for preparing a multi-level porous catalyst for directly preparing isomeric hydrocarbons from synthesis gas is carried out in the following steps: Step 1: Prepare mesoporous-macroporous SBA-15, using polystyrene beads or activated carbon particles with a diameter of 50 to 500 nm as a hard template, polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer (P123) as a soft template, and tetraethyl orthosilicate (TEOS) as a silicon source. After mixing water, hydrochloric acid, and the soft template, stir at 30 to 60 ° C to completely dissolve the soft template. Under stirring conditions, add the silicon source, and then add the hard template. Stir at 100-300 ° C to complete the reaction, and then crystallize at 150-200 ° C to obtain SBA-15. After sealing the SBA-15, place it in an oven at 100-150 ° C for 24-36 h, then filter, wash, dry, and slowly heat it to 400-650 ° C in air at a heating rate of 1-2 ° C / min and keep it warm for 5-10 h, obtaining mesoporous-macroporous SBA-15; Step 2, preparing a multi-level porous SBA-15 composed of micropores, mesopores and macropores, adding pseudo-boehmite, potassium hydroxide, and 1,-6-hexanediamine (HDA) to deionized water in sequence, stirring thoroughly to mix evenly, adding a silica sol aqueous solution, continuing to stir evenly to obtain a mixed solution, adding mesoporous-macroporous SBA-15, and dynamically crystallizing at 100~200℃ in a homogeneous reactor for 20~120h, with a rotation speed of 30~50 r / min. After the crystallization is completed, filtering and washing, drying at 80~110℃ overnight, and calcining at 500~600℃ for 10~15h to remove the template agent, to obtain a multi-level porous SBA-15 composed of micropores, mesopores and macropores; Step 3: Introduction of cobalt species: Use ultrasound-assisted vacuum impregnation to introduce active cobalt species into the straight mesoporous channels of hierarchical SBA-15 to construct a confined hierarchical cobalt-based catalyst, i.e., a hierarchical catalyst for direct production of isohydrocarbons from syngas.
[0013] In step 1, the molar ratio of the silicon source, the soft template, the hydrochloric acid (calculated as HCl), and the water is 1:0.015~0.05:5~8:120~150, and the hard template content in the SBA-15 obtained by crystallization is 10~20 wt%.
[0014] In step 2, pseudo-boehmite is calculated as Al2O3, potassium hydroxide is calculated as K2O, silica sol aqueous solution is calculated as SiO2, water includes water in the mixed solution, and the mass ratio of pseudo-boehmite, potassium hydroxide, silica sol aqueous solution, 1,-6-hexanediamine, and water is 0.0125: 0.1~0.2: 0.375~0.5: 0.2~0.5: 30~40.
[0015] In step three, the ultrasonic-assisted vacuum impregnation method is used to introduce active cobalt species into the mesoporous straight channels of the multi-level porous SBA-15. Specifically, a 0-10% auxiliary nitrate is added to a 10-30 wt% cobalt salt ethanol solution to form a cobalt salt solution, and the micropores, mesopores and macropores are vacuumed under ultrasonic conditions. When the vacuum reaches 0.05-0.1 MPa, it is maintained for 0.5-1 h, and then the cobalt salt solution is added dropwise to the micropores, mesopores and macropores to form the multi-level porous SBA-15 at a rate of 0.05-0.15 ml / min. After the addition is completed, it is maintained at a vacuum degree of 0.05-0.1 MPa for 1-3 h, and stirred at room temperature until the ethanol is completely volatilized to obtain a powder, which is calcined in an air atmosphere. The powder is heated to 80-120°C at a rate of 0.3-0.5°C / min, maintained for 2-5 h, and then heated at 0.3-0.5 The temperature was raised to 400-500 °C at a rate of ℃ / min and maintained for 6-10 h.
[0016] In step 3, the cobalt salt is one of cobalt nitrate, cobalt acetate, and cobalt chloride, or a mixture of several of them.
[0017] A multi-level porous catalyst for directly preparing isomeric hydrocarbons from synthesis gas can be used in a fixed bed reactor or a slurry bed reactor. The reduction conditions are pure hydrogen atmosphere, 200-500 ° C, 0.1-1.20 MPa, and a volume space velocity of 500-3000 h -1 (V / V), reduction for 6~24 h, when used in slurry bed, the rotation speed is 400~1400 rpm; the reaction conditions are, 150~320 ℃, 0.3~5.0Mpa, volume space velocity is 500~2000 h -1 (V / V), H2 / CO (molar ratio) = 1~3 / 1, when used in slurry bed, the rotation speed is 400~1400 rpm.
[0018] The beneficial effects of the present invention are as follows: the catalyst of the present invention has a rich micropore-mesopore-macroporous multi-level pore structure, which provides a sufficient specific surface area for the reaction, and at the same time, while obtaining highly dispersed active sites by ultrasonic-assisted vacuum impregnation, the catalyst has high thermal stability and hydrothermal stability, thereby avoiding problems such as diffusion limitation of reactants and products.
[0019] The three pore sizes of the catalyst of the present invention are adjustable (changing the crystallization temperature in the process of preparing mesoporous-macroporous SBA-15), the micropore pore size range is 0.3~1.6 nm, the mesopore pore size range is 3~25 nm, the macropore pore size range is 50~600 nm, and the catalyst specific surface area is 300~1500 m 2 / g, pore volume 0.2 ~2.5 cm 3 / g, Co3O4 grain size 2 ~10 nm, shell thickness 50 ~ 600 nm, catalyst particle diameter 50 ~ 1200 nm. It is conducive to the selective control of the synthesis of hydrocarbon compounds with different carbon number distributions.
[0020] The catalyst of the present invention has good thermal stability and hydrothermal stability. When calcined at 400-650° C. and boiled at 100-150° C. for 10 h, the multi-level pore structure of the catalyst remains substantially unchanged.
[0021] The reaction characteristics of the catalyst of the present invention are: CO conversion rate reaches 60-90%, and the mass content of the product is: CH4<5%, C2-C4<5%, C5-C 18 ≥ 60% (C5-C 18 Among them, isomeric hydrocarbons> 60%), C 18 + <30%, CO2< 2%. DETAILED DESCRIPTION Example 1
[0022] 1) Synthesis of mesoporous-macroporous SBA-15 Select polystyrene beads of 200 nm in size, polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer (P123) as soft template, tetraethyl orthosilicate (TEOS) as silicon source, the basic composition molar ratio of the reaction system is n(TEOS): n(P123): n(HC1):n(H2O)=1:0.02:5:120, and the mass percentage of the hard template is controlled to be 10wt%. First, add the above-measured H2O, HC1 and P123 into a beaker and stir for 0.5 h in a 35℃ water bath. After P123 is completely dissolved, TEOS is slowly added dropwise to the vigorously stirred solution. After TEOS is added, the hard template is added and stirred and hydrolyzed for 24 h. Then the reaction mixture is controlled to have a reaction temperature of 100℃ and a crystallization temperature of 150℃ to synthesize SBA-15 molecular sieve. The mixture was sealed and placed in an oven at 100°C for 24 h. The obtained reactants were filtered, washed and dried to obtain the sample. The sample powder was placed in a high-temperature furnace and slowly heated at a rate of 1°C / min in air. After being heated to 400°C for 5 h, the mesoporous-macroporous SBA-15 was obtained after the organic components were removed.
[0023] 2) Synthesis of multi-level pore SBA-15 A certain amount of pseudo-boehmite, KOH, and 1,-6-hexanediamine (HDA) were added to deionized water in sequence, and after being fully stirred for 15 min, the silica sol was diluted with water and added to the mixture. After 0.5 h, the above-mentioned mesoporous-macroporous SBA-15 with a content of 60 wt% was added, and the mixture was dynamically crystallized at 100 ° C for 20 h in a homogeneous reactor at a speed of 30 r / min. After the crystallization was completed, the hydrothermal kettle was taken out, filtered and washed, and then dried at 80 ° C overnight. The mass ratio of the initial raw materials for the synthesis of the multi-level pore SBA15 was controlled to be: 0.0125 units of Al2O3: 0.1 units of K2O: 0.375 units of SiO2: 0.2 units of HDA: 30 units of H2O. The above sample was calcined at 500 ° C for 10 h to remove the template agent to obtain a multi-level pore SBA-15.
[0024] 3) Introduction of cobalt species Prepare a 10 wt% cobalt nitrate ethanol solution, add 1% manganese nitrate into it, evacuate the multi-level pore SBA-15 under ultrasonic and vacuum conditions, and keep it for 0.5 h when the vacuum reaches 0.1 MPa; then add the cobalt salt ethanol solution to the multi-level pore SBA-15 at a rate of 0.05 ml / min, keep it for 1 h under vacuum, stir at room temperature until the ethanol is completely volatilized, and obtain powder, which is calcined in air atmosphere, and the powder is heated to 80 °C at a rate of 0.3 °C / min and kept for 2 h, and then heated to 400 °C at a rate of 0.3 °C / min and kept for 6 h, to obtain multi-level pore cobalt-based catalyst C-1. The structural characteristics and reaction performance of the catalyst are shown in Tables 1 and 2, respectively.
[0025] Table 1 Structural characteristics of catalysts Table 2 Fischer-Tropsch synthesis reaction results of catalysts catalyst Reaction conditions CO conversion rate % <![CDATA[CH4 %]]> <![CDATA[C 2-4 = %]]> <![CDATA[C5- 18 %]]> <![CDATA[C 5-18 Isohydrocarbon content]]> <![CDATA[CO2 %]]> Example 1 <![CDATA[150℃,1000h -1 ,]]> 45 4.8 4.2 62 63 1.2 Example 2 <![CDATA[300℃,2000h -1 ,]]> 80 4.5 72 65 66 1.5 Example 3 <![CDATA[250℃,1200h -1 ,]]> 60 4.5 73 65 62 1.3 Example 4 <![CDATA[230℃,1500h -1 ,]]> 70 4.3 76 67 65 1.2 Example 2
[0026] 1) Synthesis of mesoporous-macroporous SBA-15 500 nm polystyrene beads were selected as hard templates, polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer (P123) was selected as soft templates, tetraethyl orthosilicate (TEOS) was selected as silicon source, and the basic composition molar ratio of the reaction system was n (TEOS): n (P123): n (HC1): n (H2O) = 1: 0.05: 8: 150, and the mass percentage of the hard template was controlled to be 20 wt%. First, H2O, HC1 and P123 were added to a beaker according to the above measurement, and stirred in a 60℃ water bath for 1 h. After P123 was completely dissolved, TEOS was slowly added dropwise to the vigorously stirred solution. After TEOS was added, the hard template was added and the stirring and hydrolysis were continued for 36 h. Then the reaction mixture was controlled to have a reaction temperature of 300 °C and a crystallization temperature of 200 °C to synthesize an ordered macroporous-mesoporous structure SBA-15 molecular sieve with adjustable macropore and mesopore pore sizes. The reaction mixture was filtered, washed and dried to obtain a sample. The sample powder was placed in a high-temperature furnace and slowly heated at a heating rate of 2°C / min in air. After being heated to 650°C for 10 hours, the mesoporous-macroporous SBA-15 after the organic components were removed was obtained.
[0027] 2) Synthesis of multi-level pore SBA-15 A certain amount of pseudo-boehmite, KOH, and 1,-6-hexanediamine (HDA) were added to deionized water in sequence, and after being fully stirred for 30 min, the silica sol was diluted with water and added to the mixture. After 1.5 h, the above-mentioned mesoporous-macroporous SBA-15 with a content of 85 wt% was added, and the mixture was dynamically crystallized at 200 °C for 120 h in a homogeneous reactor with a rotation speed of 50 r / min. After the crystallization was completed, the hydrothermal kettle was taken out, filtered and washed, and then dried at 110 °C overnight. The mass ratio of the initial raw materials for the synthesis of the multi-level porous SBA15 was controlled to be: 0.0125 units of Al2O3: 0.2 units of K2O: 0.5 units of SiO2: 0.5 units of HDA: 40 units of H2O. The above sample was calcined at 600 °C for 15 h to remove the template agent to obtain the multi-level porous SBA-15.
[0028] A 30 wt% cobalt acetate ethanol solution was prepared, and a 3% auxiliary agent ruthenium nitrate was added thereto. Under ultrasonic and vacuum conditions, the multi-level pore SBA-15 was evacuated. When the vacuum reached 0.1 MPa, it was maintained for 1 h. Then, the cobalt salt ethanol solution was added to the multi-level pore SBA-15 at a rate of 0.15 ml / min. After the addition was completed, it was maintained under vacuum for 3 h. The powder was stirred at room temperature until the ethanol was completely volatilized to obtain a powder. The powder was calcined in an air atmosphere. The powder was heated to 120 °C at a rate of 0.5 °C / min and maintained for 5 h. Then, the powder was heated to 500 °C at a rate of 0.5 °C / min and maintained for 10 h. The multi-level pore cobalt-based catalyst C-2 was obtained. The structural characteristics and reaction performance of the catalyst are shown in Tables 1 and 2, respectively. Example 3
[0029] 1) Synthesis of mesoporous-macroporous SBA-15 Activated carbon particles with a size of 300 nm were selected as hard templates, triblock copolymers of polyethylene oxide-polypropylene oxide-polyethylene oxide (P123) were selected as soft templates, tetraethyl orthosilicate (TEOS) was selected as silicon source, and the basic composition molar ratio of the reaction system was n (TEOS): n (P123): n (HC1): n (H2O) = 1: 0.04: 8: 150, and the mass percentage of the hard template was controlled to be 20 wt%. First, H2O, HC1 and P123 were added to a beaker according to the above measurement, and stirred in a 50℃ water bath for 1 h. After P123 was completely dissolved, TEOS was slowly added dropwise to the vigorously stirred solution. After the addition of TEOS was completed, the hard template was added, and the stirring and hydrolysis were continued for 30 h. Then the reaction mixture was controlled to have a reaction temperature of 280°C and a crystallization temperature of 200°C to synthesize an ordered macroporous-mesoporous SBA-15 molecular sieve with adjustable macropore and mesopore pore sizes. The reaction mixture was filtered, washed and dried to obtain a sample. The sample powder was placed in a high-temperature furnace and slowly heated at a heating rate of 1.5°C / min in air until it reached 630°C and was kept warm for 10 hours to obtain the mesoporous-macroporous SBA-15 after the organic components were removed.
[0030] 2) Synthesis of multi-level pore SBA-15 A certain amount of pseudo-boehmite, KOH, and 1,-6-hexanediamine (HDA) were added to deionized water in sequence, and after being fully stirred for 30 min, the silica sol was diluted with water and added to the mixture. After 1.5 h, the above-mentioned mesoporous-macroporous SBA-15 with a content of 85 wt% was added, and the mixture was dynamically crystallized at 200 °C for 120 h in a homogeneous reactor with a rotation speed of 50 r / min. After the crystallization was completed, the hydrothermal kettle was taken out, filtered and washed, and then dried at 110 °C overnight. The mass ratio of the initial raw materials for the synthesis of the multi-level porous SBA15 was controlled to be: 0.0125 units of Al2O3: 0.18 units of K2O: 0.5 units of SiO2: 0.5 units of HDA: 40 units of H2O. The above sample was calcined at 500 °C for 15 h to remove the template agent to obtain a multi-level porous SBA-15.
[0031] Prepare a 25 wt% cobalt nitrate ethanol solution, add 2% auxiliary lanthanum nitrate, evacuate the multi-level pore SBA-15 under ultrasonic and vacuum conditions, and keep it for 1 hour when the vacuum reaches 0.08 MPa; then add the cobalt salt ethanol solution to the multi-level pore SBA-15 at a rate of 0.15 ml / min, keep it under vacuum for 3 hours after the addition is complete, stir at room temperature until the ethanol is completely volatilized, obtain powder, calcine in air atmosphere, heat the powder to 120 ℃ at a rate of 0.5 ℃ / min and keep it for 3 hours, then heat it to 500 ℃ at a rate of 0.5 ℃ / min and keep it for 10 hours, and obtain multi-level pore cobalt-based catalyst C-3. The structural characteristics and reaction performance of the catalyst are shown in Tables 1 and 2, respectively. Example 4
[0032] 1) Synthesis of mesoporous-macroporous SBA-15 Activated carbon particles with a size of 300 nm were selected as hard templates, triblock copolymers of polyethylene oxide-polypropylene oxide-polyethylene oxide (P123) were selected as soft templates, tetraethyl orthosilicate (TEOS) was selected as silicon source, and the basic composition molar ratio of the reaction system was n (TEOS): n (P123): n (HC1): n (H2O) = 1: 0.03: 8: 150, and the mass percentage of the hard template was controlled to be 20 wt%. First, H2O, HC1 and P123 were added to a beaker according to the above measurement, and stirred in a 50℃ water bath for 1 h. After P123 was completely dissolved, TEOS was slowly added dropwise to the vigorously stirred solution. After the addition of TEOS was completed, the hard template was added, and the stirring and hydrolysis were continued for 30 h. Then the reaction mixture was controlled to have a reaction temperature of 250 °C and a crystallization temperature of 200 °C to synthesize an ordered macroporous-mesoporous structure SBA-15 molecular sieve with adjustable macropore and mesopore diameters. The mixture was sealed with a lid and placed in an oven for 25 h at 120 °C. The obtained reactants were filtered, washed, and dried to obtain a sample. The sample powder was placed in a high-temperature furnace and slowly heated at a heating rate of 1.5 °C / min in air. After being heated to 630 °C for 10 h, the mesoporous-macroporous SBA-15 after the organic components were removed was obtained.
[0033] 2) Synthesis of multi-level pore SBA-15 A certain amount of pseudo-boehmite, KOH, and 1,-6-hexanediamine (HDA) were added to deionized water in sequence. After being fully stirred for 30 min, the silica sol was diluted with water and added to the mixture. After 1.5 h, the above-mentioned mesoporous-macroporous SBA-15 with a content of 85 wt% was added, and the mixture was dynamically crystallized at 200 °C for 100 h in a homogeneous reactor with a rotation speed of 50 r / min. After the crystallization was completed, the hydrothermal kettle was taken out, filtered and washed, and then dried at 110 °C overnight. The mass ratio of the initial raw materials for synthesizing the multi-level porous SBA15 was controlled to be: 0.0125 units of Al2O3: 0.18 units of K2O: 0.45 units of SiO2: 0.5 units of HDA: 40H2O. The above sample was calcined at 500 °C for 15 h to remove the template agent to obtain the multi-level porous SBA-15.
[0034] 3) Introduction of cobalt species Prepare a 20 wt% cobalt chloride ethanol solution, add 2% auxiliary magnesium nitrate, evacuate the multi-level pore SBA-15 under ultrasonic and vacuum conditions, and keep it for 1 hour when the vacuum reaches 0.08 MPa; then add the cobalt salt ethanol solution to the multi-level pore SBA-15 at a rate of 0.12 ml / min, keep it for 3 hours under vacuum conditions, stir at room temperature until the ethanol is completely volatilized, obtain powder, calcine in air atmosphere, heat the powder to 120 ℃ at a rate of 0.3 ℃ / min and keep it for 3 hours, then heat it to 500 ℃ at a rate of 0.5 ℃ / min and keep it for 10 hours, and obtain multi-level pore cobalt-based catalyst C-4. The structural characteristics and reaction performance of the catalyst are shown in Tables 1 and 2, respectively.
Claims
1. A multi-level porous catalyst for direct production of isohydrocarbons from synthesis gas, characterized in that: The multi-level porous catalyst is composed of active components, additives and carriers, and the composition by weight percentage is as follows: metal cobalt: 2-30%, metal additive content 0-10%, shell carrier 65-90%, the carrier is a multi-level porous SBA-15 composed of micropores, mesopores and macropores; metal cobalt and metal additives are used as the inner core and are wrapped by the shell carrier, the particle diameters of the metal cobalt and metal additives are 2-10 nm, and the thickness of the shell carrier is 50-600 nm.
2. The multi-level porous catalyst for direct synthesis of isohydrocarbons from synthesis gas according to claim 1, characterized in that: The multi-level porous catalyst has a specific surface area of 300-1500 m2 / g, a pore volume of 0.2-2.5 cm3 / g, a micropore size of 0.3-1.6 nm, a mesopore size of 3-25 nm, a macropore size of 50-600 nm, and a catalyst particle diameter of 50-1200 nm.
3. The multi-level porous catalyst for direct synthesis of isohydrocarbons from synthesis gas according to claim 1, characterized in that: The metal additive is one or two of manganese, zirconium, silver, ruthenium, lanthanum, cerium, calcium, magnesium, barium and the like.
4. The multi-level porous catalyst for direct synthesis of isohydrocarbons from synthesis gas according to claim 1, characterized in that: The hierarchical pore structure of the multi-level porous catalyst remains unchanged when the catalyst is calcined at 400-650 °C, and the hierarchical pore structure of the catalyst remains unchanged when the catalyst is boiled under hydrothermal conditions at 100-150 °C for 10 h.
5. The multi-level porous catalyst for direct synthesis of isohydrocarbons from synthesis gas according to claim 1, characterized in that: When the multi-level porous catalyst is used, the CO conversion rate reaches 60-90%, and the mass percentage content of the product is: CH4<5%, C2-C4<5%, C5-C 18 ≥ 60%, C 18 + <30%, CO2< 2%.
6. A method for preparing the multi-level porous catalyst for directly converting synthesis gas into isohydrocarbons as claimed in claim 1, characterized in that: Follow the steps below Step 1: Prepare mesoporous-macroporous SBA-15, using polystyrene beads or activated carbon particles with a diameter of 50 to 500 nm as a hard template, polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer (P123) as a soft template, and tetraethyl orthosilicate (TEOS) as a silicon source. After mixing water, hydrochloric acid, and the soft template, stir at 30 to 60 ° C to completely dissolve the soft template. Under stirring conditions, add the silicon source, and then add the hard template. Stir at 100-300 ° C to complete the reaction, and then crystallize at 150-200 ° C to obtain SBA-15. After sealing the SBA-15, place it in an oven at 100-150 ° C for 24-36 hours, then filter, wash, dry, and slowly heat it to 400-650 ° C in air at a heating rate of 1-2 ° C / min and keep it warm for 5-10 h, obtaining mesoporous-macroporous SBA-15; Step 2, preparing a multi-level porous SBA-15 composed of micropores, mesopores and macropores, adding pseudo-boehmite, potassium hydroxide and 1,-6-hexanediamine (HDA) to deionized water in sequence, stirring thoroughly to mix evenly, adding a silica sol aqueous solution, continuing to stir evenly to obtain a mixed solution, adding mesoporous-macroporous SBA-15, and dynamically crystallizing at 100~200℃ in a homogeneous reactor for 20~120h, with a rotation speed of 30~50 r / min. After the crystallization is completed, filtering and washing, drying at 80~110℃ overnight, and calcining at 500~600℃ for 10~15h to remove the template agent, to obtain a multi-level porous SBA-15 composed of micropores, mesopores and macropores; Step 3: Introduction of cobalt species: Use ultrasound-assisted vacuum impregnation to introduce active cobalt species into the straight mesoporous channels of hierarchical SBA-15 to construct a confined hierarchical cobalt-based catalyst, i.e., a hierarchical catalyst for direct production of isohydrocarbons from syngas.
7. The method for preparing a multi-level porous catalyst for directly converting synthesis gas into isohydrocarbons according to claim 6, characterized in that: In step 1, the molar ratio of the silicon source, the soft template, the hydrochloric acid (calculated as HCl), and the water is 1:0.015~0.05:5~8:120~150, and the hard template content in the SBA-15 obtained by crystallization is 10~20 wt%.
8. The method for preparing a multi-level porous catalyst for directly converting synthesis gas into isohydrocarbons according to claim 7, characterized in that: In step 2, pseudo-boehmite is calculated as Al2O3, potassium hydroxide is calculated as K2O, silica sol aqueous solution is calculated as SiO2, water includes water in the mixed solution, and the mass ratio of pseudo-boehmite, potassium hydroxide, silica sol aqueous solution, 1,-6-hexanediamine, and water is 0.0125: 0.1~0.2: 0.375~0.5: 0.2~0.5: 30~40.
9. The method for preparing a multi-level porous catalyst for directly converting synthesis gas into isohydrocarbons according to claim 6, characterized in that: In step three, the ultrasonic-assisted vacuum impregnation method is used to introduce active cobalt species into the mesoporous straight channels of the multi-level porous SBA-15. Specifically, a 0-10% auxiliary nitrate is added to a 10-30 wt% cobalt salt ethanol solution to form a cobalt salt solution, and the micropores, mesopores and macropores are vacuumed under ultrasonic conditions. When the vacuum reaches 0.05-0.1 MPa, it is maintained for 0.5-1 h, and then the cobalt salt solution is added dropwise to the micropores, mesopores and macropores to form the multi-level porous SBA-15 at a rate of 0.05-0.15 ml / min. After the addition is completed, it is maintained at a vacuum degree of 0.05-0.1 MPa for 1-3 h, and stirred at room temperature until the ethanol is completely volatilized to obtain a powder, which is calcined in an air atmosphere. The powder is heated to 80-120°C at a rate of 0.3-0.5°C / min, maintained for 2-5 h, and then heated at 0.3-0.5 The temperature is raised to 400-500°C at a rate of ℃ / min and maintained for 6-10 hours; the cobalt salt is one of cobalt nitrate, cobalt acetate and cobalt chloride or a mixture of several thereof.
10. An application of a multi-level porous catalyst for direct production of isohydrocarbons from synthesis gas, characterized in that: It can be used in fixed bed reactor or slurry bed reactor. The reduction conditions are pure hydrogen atmosphere, 200~500 ℃, 0.1~1.20 Mpa, and volume space velocity of 500~3000 h -1 (V / V), reduction for 6~24 h, when used in slurry bed, the rotation speed is 400~1400 rpm; the reaction conditions are 150~320℃, 0.3~5.0 Mpa, and the volume space velocity is 500~2000 h -1 (V / V), H2 / CO (molar ratio) = 1~3 / 1, when used in slurry bed, the rotation speed is 400~1400 rpm.
Citation Information
Patent Citations
Hydrocarbon catalyst containing high content isomeric hydrocarbon prepared from synthesis gas and preparation method and use
CN101327442A